Social relations network in building civilization an analysis of its significance - Berghout, Abdul Aziz; Berghout, Zakia (International Islamic University Malaysia (IIUM), 2016)
This paper introduces the concept of social relations network as an important el-ement in the process of building a civilisation. In general terms, any human society em-barking on a civilizing process needs, among other things, four integral ingredients namely people, ideas, objects and social relations network. The realm of persons pro-vides the human capital and talents. The realm of ideas offers worldviews, ideologies, philosophies, visions, concepts, values, and perspectives. Whereas, the realm of objects makes available things, tools, products, know-how, instruments and the necessary needs of a society. However, these three important realms remain mere isolated elements in the absence of the fourth realm that synthesises and articulates them in the form of a civilising project leading to the development of society. This fourth realm is but the social relations network that integrates and puts persons, ideas and objects together in a bid to build a civilisation. This paper uses textual analysis to examine the notion of so-cial relations network and its function in the process of building civilisation. It draws a special attention to the views of Malik Bennabi and his understanding of and approach to the notion of social relations network and how it works in making a civilisation.